SINDROME NEFRÓTICO EN NIÑOS: ROL DEL PEDIATRA Y NEFRÓLOGO PEDIATRA - L, Cisneros, (2018)
Abstract Nephrotic syndrome in children is a very frequent pathology in our environment. The initial approach, usually, is performed by the pediatrician or general practitioner, until it is evaluated by the pediatric nephrologist and / or nephrologist of adults with training in pediatrics; so in this review some guidelines are outlined to standardize their initial study, edema control and treatment until their evaluation by the specialty, through an adequate reference and counter-referral system, guaranteeing the adherence of the child and his family, is special in those who live in remote places with reduced access to health systems on an ongoing basis. Key words: Nephrotic syndrome; Child; Role of the pediatrician; Role of the nephrologist. (source: MeSH NLM) DOI: https://doi.org/10.25176/RFMH.v18.n1.1270